Echocardiographic Features of Cardiac Angiosarcomas: The Mayo Clinic Experience (1976–2013). Issue 2 (13th October 2015) - Kupsky, Daniel F.; Newman, Darrell B.; Kumar, Gautam; Maleszewski, Joseph J.; Edwards, William D.; Klarich, Kyle W.
Abstract : Objective: Cardiac angiosarcoma is the most common primary malignant cardiac tumor. The dismal prognosis and nonspecific symptomatology underscore the need for an accurate and cost‐effective approach to the identification and characterization of this rare tumor. Methods: Mayo Clinic tissue registry archives were queried for all histologically confirmed cases of cardiac angiosarcoma (1976–2013) with available imaging data. Echocardiograms were retrospectively reviewed. Results: Thirty‐three cases of cardiac angiosarcoma were identified; of these, 17 had echocardiograms available (mean age, 46 years; six men). Transthoracic echocardiography (TTE) as the initial diagnostic test had 75% sensitivity for visualizing primary cardiac angiosarcoma (9/12 patients). Tumor extension into the pericardium was common and pericardial effusion was present in 15 patients (88%); however, pericardial fluid cytology was negative for malignancy in all tested patients (n = 15). Left ventricular ejection fraction (LVEF) was preserved in 16 patients (94%) (average LVEF, 62%). Right ventricular function was mildly reduced in two patients (12%) at initial presentation. Tricuspid valve obstruction was present in three patients (18%; mean diastolic gradient, 6.3 mmHg [range, 3–11 mmHg]). Conclusion: The sensitivity of TTE as the first diagnostic imaging modality compared favorably with computed tomography. Pericardial effusion was common, but pericardial fluid cytology was negative in all patients who underwent pericardiocentesis. The absence of a stalk was a universal finding that may help distinguish angiosarcoma from benign, primarily pedunculated tumors such as myxoma and papillary fibroelastoma.